Incidencia de la violencia intrafamiliar en el rendimiento escolar de estudiantes de 9no egb, colegio “9 de octubre”, machala - 2024 - Franco Benenaula, Joselyn Amanda (Machala, 2025)
Domestic violence is a prevalent issue in society that affects many families. It refers to any form of abuse that occurs within the household. This type of violence includes physical, psychological, sexual, and economic harm, which also impacts the academic performance of children and adolescents. This effect is reflected in their activities and behaviors within the educational environment. Despite efforts to eradicate its negative impact on society, the high incidence of domestic violence remains evident. Education is fundamental to the development of society, and it is the responsibility of families, schools, and the community to ensure that students can learn in a safe and violence-free environment. If measures are not taken to address this issue, the impact of domestic violence will continue to affect generations of students, hindering their personal and academic growth. This research focuses on the prevention of domestic violence and its impact on academic performance among students at "9 de Octubre" School in Machala. The objective is to analyze the relationship between domestic violence and low academic performance, which significantly affects students' behavior, leading to consequences such as anxiety, absenteeism, low self-esteem, and a noticeable decline in academic activities. The statistical results indicate a lack of awareness about the types of violence. Therefore, it is considered necessary to intervene by providing information to the educational community, fostering a better understanding of the issue, and generating a supportive change within its environment. To diagnose the problem, a mixed-methods approach was implemented, utilizing techniques and tools such as surveys directed at ninth-grade students, interviews with teachers and student counseling department staff, and observations within the school environment. These methods helped identify awareness of this issue, which often goes unreported due to fear, lack of knowledge, or insufficient support. In response to this problem, an intervention plan was proposed and implemented through the dissemination of an informational guide titled "The Importance of Understanding Domestic Violence." This guide was designed to help students identify different forms of violence, learn about their rights, and understand the steps to take if they witness any form of violence. Additionally, it aimed to strengthen the student counseling department (DECE) by providing spaces for active listening and support with respect, empathy, and effective communication. This initiative seeks to assist students facing domestic violence and contribute to reducing this issue. Therefore, it is essential for educational institutions to take an active role in the prevention and response to domestic violence by creating spaces for information and support to reduce its incidence and mitigate its negative effects in the educational setting. By doing so, it will be possible to improve the quality of education and provide students with the necessary tools to overcome difficulties they face at home, allowing them to develop in a safe and conducive learning environment.
La violencia intrafamiliar es un tema presente en la sociedad, que afecta a muchas familias y que se refiere a cualquier tipo de abuso que ocurre dentro del hogar. Este tipo de violencia incluye daños físicos, psicológicos, sexuales y económicos, que impacta también el desempeño escolar niños, niñas y adolescentes, lo cual se ve reflejado en sus actividades y comportamientos dentro del ámbito educativo. A pesar de los intentos por erradicar el impacto negativo en la sociedad de esta forma de violencia, aun es notable el alto nivel de incidencia de la violencia intrafamiliar. La educación es fundamental para el desarrollo de la sociedad y es responsabilidad de la familia, colegio y la comunidad garantizar que los estudiantes puedan aprender en un entorno seguro y libre de violencia. Si no se toman medidas para abordar esta problemática, el impacto de la violencia intrafamiliar seguirá afectando a generaciones de estudiantes, impidiendo su crecimiento personal y académico. La presente investigación se enfoca en la prevención de la violencia intrafamiliar y su impacto en el rendimiento académico en los estudiantes del Colegio “9 de octubre” de Machala, con el propósito de analizar la relación entre la violencia intrafamiliar y el bajo rendimiento académico que afecta significativamente el comportamiento de los estudiantes, provocando consecuencias como ansiedad, ausentismo, baja autoestima y un notable descenso en las actividades académicas. Los resultados de las estadísticas indican el desconocimiento que existe sobre los tipos de violencia, es así se considera intervenir, generando información ante la comunidad educativa, comprendiendo más sobre la problemática, generado un cambio de apoyo dentro de su entorno. Para realizar un diagnóstico de la problemática se implementó una metodología con un enfoque mixto, utilizando técnicas y herramienta como la encuesta dirigida a los estudiantes de 9no EGB, la entrevista a docentes y personal del Departamento de consejería estudiantil y observación dentro del entorno escolar, para identificar sobre el conocimiento de esta situación, la cual la mayoría no son denunciados ya sea por miedo, desconocimiento o falta de apoyo. Ante esta problemática se propuso el plan de intervención que se llevó a cabo, a través de la socialización de un instructivo informativo llamado “La importancia del conocimiento de la violencia intrafamiliar”, diseñado para que los estudiantes puedan identificar las distintas formas de violencia que existen, conocer sus derechos y las rutas que se deben seguir en caso de presenciar un tipo de violencia, para fortalecer el DECE, brindando espacios de escucha activa y apoyo con respeto, empatía y comunicación efectiva para los estudiantes que enfrentan violencia intrafamiliar ayudando a reducir esta problemática. Por lo tanto, es necesario que dentro de las instituciones educativas se asuma un rol activo de activo en la prevención y atención de la violencia intrafamiliar generando espacios de información y apoyo para reducir su incidencia y mitigar sus efectos negativos en el ámbito educativo. De esta manera será posible mejorar la calidad educativa y apoyar a los estudiantes con herramientas necesarias para superar dificultades que enfrentan en sus hogares, permitiéndoles desarrollarse en un ambiente seguro y propicio para su aprendizaje.
Keywords: TRABAJO SOCIAL; VIOLENCIA INTRAFAMILIAR; COMUNIDAD EDUCATIVA; PREVENCION